Application of cup-shaped trilactams for selective extraction of volatile compounds by gas chromatography-mass spectrometry. Issue 20 (17th August 2020) - Sartyoungkul, Sitanan; Thaveesangsakulthai, Isaya; Cabello, Mark Kristan Espejo; Kulsing, Chadin; Sakurai, Hidehiro
Abstract : Chiral cup-shaped trilactams were used as liquid phase extraction material of volatile organic compounds in perfume analyzed by SPME GC-MS. (+)-material showed higher selective chiral recognition with oxygenated and cyclic volatile compounds. Abstract : Chiral cyclic trilactams ((+)-1 and (−)-1 ) with C 3 symmetry were investigated as liquid phase extraction materials of volatile compounds. Perfume samples, involving a range of chiral odor active terpenoids, were applied and each sample before and after the liquid phase extraction was analyzed by solid phase microextraction (SPME)-gas chromatography hyphenated with mass spectrometry. It was found that (+)-1 exhibited significantly higher enrichment factors for several terpenoids, while (−)-1 did not. The mode of interactions between each enantiomer and l -menthol and Kharismal (methyl dihydrojasmonate) was further investigated by molecular dynamics (MD) simulations and theoretical density functional theory (DFT) calculations, showing the favorable interactions of enriched substrates with (+)-1 through noncovalent interactions, either hydrogen bonds or electrostatic interactions.